ОСОБЛИВОСТІ ЕЛЕКТРОМАГНІТНОЇ СУМІСНОСТІ НАПІВПРОВІДНИКОВИХ ПЕРЕТВОРЮВАЧІВ У СТРУКТУРАХ ІЗ БЕЗПРОВОДОВИМИ КАНАЛАМИ - Бакіко, В.М.; Попович, П.В.; Швайченко, В.Б. (Інститут електродинаміки НАН України, Київ, 2019)
The features of the problem of electromagnetic compatibility of semiconductor converters, caused by the disturbance situation in the process of operating systems with a wireless channel, are determined. The simulation of the process oftransmitting information in modern and future channels of the GSM, Wi-Fi, WiMAX technologies under the influence ofinterference with various probabilistic characteristics has been carried out. Simulation models of the Matlab application program are given, taking into account the features of communication channels, modulations and law of distribution of interference. It is shown that the reliability of the transmission significantly depends on the features of the law of distribution of interference. Recommendations for improving the structure of systems with the transfer of information on promising technologies are proposed. References 5, figures 5.